A brief overview on the utilization of high strength steel (HSS) for automotive structural welding applications - M. N. M., Salleh; M., Ishak; M. M., Quazi (Springer, 2023)
High-strength steels are now increasingly used in automotive structural applications owing to their resilience, crashworthiness, and ease of manufacturing. This paper reviews the application of high-strength steels for the automotive structure, describing the condition of the steel after been put in the car structures. Thereafter, the importance of advanced high strength boron steel is highlighted, and its weldability is discussed. Current issues related to welding and changes in microstructure are discussed. It is imperative that Boron steel is gaining widespread attention due to its good mechanical characteristic in car structures and its weldability remains a topic of significant research interest. Lastly, the important considerations are summarized.